2022
DOI: 10.1002/cptc.202200007
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Oleate Synthesis by TiO2 Photocatalytic Esterification of Oleic Acid: Optimisation by Response Surface Quadratic Methodology, Reaction Kinetics and Thermodynamics

Abstract: Methyl oleate, an example of a FAME (fatty acid methyl ester), was produced by oleic acid (OA) photoesterification with TiO2 and UVA light. Different parameters were evaluated and optimised: catalyst pretreatment, temperature (25–65 °C), catalyst loading (1–30 % w/wOA) and oleic acid : alcohol molar ratio (1 : 3–1 : 55). Response surface quadratic methodology obtained by central composite rotational design (RSM‐CCRD) was used to evaluate the main operational conditions of the photoesterification process. A hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
(155 reference statements)
0
6
0
Order By: Relevance
“…Table 3 indicates the ANOVA results for the yield of OA to biodiesel. At the 95% confidence level, the regression model's F-value (Fischer test, which determines the significance of the chosen model and individual parameter affecting the response) of 295.47 and p-value < 0.0001 (probability of error, with < 0.05 representing significance) shows that it is statistically significant 62 , 63 . As shown in Table 3 , A, C, D, AB, AC, AD, BC, BD, CD, A 2 , B 2 , C 2 , and D 2 are significant, while B is not a significant model term.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 indicates the ANOVA results for the yield of OA to biodiesel. At the 95% confidence level, the regression model's F-value (Fischer test, which determines the significance of the chosen model and individual parameter affecting the response) of 295.47 and p-value < 0.0001 (probability of error, with < 0.05 representing significance) shows that it is statistically significant 62 , 63 . As shown in Table 3 , A, C, D, AB, AC, AD, BC, BD, CD, A 2 , B 2 , C 2 , and D 2 are significant, while B is not a significant model term.…”
Section: Resultsmentioning
confidence: 99%
“…Tere have been numerous studies on the esterifcation of oleic acid conducted at both mild and supercritical temperatures. However, it is frequently observed that the increase in temperature has been found to be advantageous, as demonstrated by Tesser et al [43], Hassan and Vinjamur [44], and Welter et al [45]. Higher temperatures and pressures increase the kinetic energy of molecules, improving the frequency of efective collisions and resulting in higher conversion values.…”
Section: Evaluation Of the Operating Variables Of The Atomizationmentioning
confidence: 98%
“…More recently their application as part of biofuel is reported [ 143 ]. Fatty acid methyl esters (FAME) can be obtained by photocatalytic esterification to produce biodiesel [ 144 , 145 , 146 ].…”
Section: Fatty Acidsmentioning
confidence: 99%